2010
DOI: 10.1016/j.ccr.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Inhibition of the Anaphase-Promoting Complex Induces A Spindle Checkpoint-Dependent Mitotic Arrest in the Absence of Spindle Damage

Abstract: Summary Microtubule inhibitors are important cancer drugs that induce mitotic arrest by activating the spindle assembly checkpoint (SAC), which in turn inhibits the ubiquitin ligase activity of the Anaphase-Promoting Complex (APC). Here we report a small molecule, Tosyl-L-Arginine Methyl Ester (TAME), which binds to the APC and prevents its activation by Cdc20 and Cdh1. A prodrug of TAME arrests cells in metaphase without perturbing the spindle, but nonetheless the arrest is dependent on the SAC. Metaphase arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
330
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(371 citation statements)
references
References 46 publications
29
330
2
Order By: Relevance
“…Although these data indicate that APC/C regulates centrosome clustering and the formation of bipolar spindle in CA cells, the actual 'effector' protein, which is regulated by APC/C, remained unknown. We observed that the spindle morphology induced by APC/C knockdown or treatment with the APC/C-CDC20/CDH1 inhibitor proTAME 11,12 showed a well-structured threefold or fourfold rotational symmetry and the spindle poles clearly located at the periphery of the DNA (Figs 1d and 2a; and Supplementary Fig. 3a).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Although these data indicate that APC/C regulates centrosome clustering and the formation of bipolar spindle in CA cells, the actual 'effector' protein, which is regulated by APC/C, remained unknown. We observed that the spindle morphology induced by APC/C knockdown or treatment with the APC/C-CDC20/CDH1 inhibitor proTAME 11,12 showed a well-structured threefold or fourfold rotational symmetry and the spindle poles clearly located at the periphery of the DNA (Figs 1d and 2a; and Supplementary Fig. 3a).…”
Section: Resultsmentioning
confidence: 84%
“…The major role of APC/C-CDC20 is to initiate transition from metaphase to anaphase via targeting for degradation several mitotic proteins, such as cyclin B and Securin. Genetic ablation, knockdown or inhibition of CDC20 results in metaphase arrest and cell death that is associated with stabilization of APC/C-CDC20 substrates 11,12,37 . In addition, genetic ablation of CDC20 results in complete tumour regression in mice in comparison with treatment with taxol, vincristine or BI2536, which only induces partial responses 37 .…”
Section: Ub-eg5mentioning
confidence: 99%
“…These results have been reinforced with the discovery of tosyl-L-arginine methyl ester (TAME), an APC/C small-molecule inhibitor that efficiently arrests tumor cells in mitosis triggering cell death. 73 Although targeting mitotic exit may be highly efficient, how can this strategy discriminate between tumor and normal proliferating cells? As previously suggested, APC/C-Cdc20 inhibitors could be useful in combination with other mitotic poisons by slowing cyclin B1 degradation and thus providing enough time to reach the apoptotic threshold of tumor cells.…”
Section: Cell Deathmentioning
confidence: 99%
“…27 For these reasons, to block mitotic exit, we opted for the pharmacological inhibition of the APC/C with a previously characterized inhibitor, proTAME. 40 Since manipulation of mitotic block seems to be a promising approach to kill cancerous cells, in this paper we attempted to answer the questions: What is the best strategy to induce mitotic death, by extending the mitotic block or by enhancing mitotic exit? Which one would synergize best with antimitotic drugs?…”
Section: Introductionmentioning
confidence: 99%